1999
DOI: 10.1007/s11908-999-0049-8
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence among HIV-infected patients: Understanding the complex behavior of patients taking this complex therapy

Abstract: Adherence to antiretroviral regimens by HIV-infected patients is necessary to prolong viral suppression and forestall viral resistance. This review covers the major advances made in research on adherence to HIV therapy in the past year. Currently, approximately 40% of patients receiving antiretroviral therapy have significant problems with adherence. Established predictors of poor adherence include depression, alcohol and illicit drug use, poor self-efficacy, and certain health beliefs. Medical providers are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…It is possible that factors such as self-efficacy, 34 the ability to express emotions, 35 differing cultural expressions of psychological distress 36 and complex adherence behaviour 37 influenced results. Another reason could be that few other studies exploring the risk of non-adherence in depressed patients have excluded participants who recently started ART.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that factors such as self-efficacy, 34 the ability to express emotions, 35 differing cultural expressions of psychological distress 36 and complex adherence behaviour 37 influenced results. Another reason could be that few other studies exploring the risk of non-adherence in depressed patients have excluded participants who recently started ART.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to factors associated with ART adherence, important considerations are positive attitude about treatment 119 and medication reminders 106,108,120,121 . Forgetfulness is a common reason for missing or skipping a dose, and is a frequently cited reason for lack of adherence across HIV infected populations 106,107,108,121,122,123 .…”
Section: Adherencementioning
confidence: 99%
“…Forgetfulness is a common reason for missing or skipping a dose, and is a frequently cited reason for lack of adherence across HIV infected populations 106,107,108,121,122,123 . Assistance with adherence and addressing ongoing illicit drug use may enable occasional users to be more adherent to their antiretrovirals.…”
Section: Adherencementioning
confidence: 99%
“…While other studies have demonstrated the negative effect of alcohol 24 and illicit drugs on access to and adherence with ART, [25][26][27][28][29][30][31][32][33] this small pilot study suggests that gaining access to ART in a trusted setting may promote positive health behaviors (e.g., seeking and gaining access to drug treatment) and result in improved health outcomes among active drug users. In our study, the proportion of individuals who achieved an HIV-1 RNA level below the level of detection and an increase of the CD4 lymphocytes count is similar to results obtained in clinical trials in highly selected non-IDU patients.…”
Section: Discussionmentioning
confidence: 73%